Case report and literature review: Asymptomatic littoral cell angioma in a 3-year-old girl - Yanling Mou; Liucheng Yang; Jianjun Wang; Qinming Chen; Mengzhen Zhang; Xi Zhang; Rongying Tan; Djibril Adam Mahamat; Kai Wu (Frontiers Media S.A., 2024)
BackgroundLittoral cell angioma (LCA) is an extremely uncommon benign vascular tumor of the spleen. Cases of LCA in infants are rarely reported, and due to the rarity of the tumor and non-specific symptoms, the diagnosis of LCA is often overlooked in clinical practice.Case reportWe present a 3-year-old girl with pulmonary inflammation who was admitted to the hospital due to the discovery of a space-occupying lesion in the spleen. Pathology after splenectomy confirmed LCA, and there was no recurrence observed at the 5-month follow-up examination.ConclusionLCA should be considered when a child shows asymptomatic splenomegaly, with antigen expression indicating dual positivity of endothelial and histiocytic markers. Laparoscopic splenectomy remains the primary method of treating LCA.